ANALISIS PENGARUH PEMANFAATAN MEDIA SOSIAL DALAM PENYEBARAN LAYANAN INFORMASI PUBLIK DI PEMERINTAH - Wulur, Frando Christo; Mulyanti, Dety (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
In this era of technological advances, information can be easily disseminated via the internet. Social media is one of the options used by the government to communicate with the public and carry out its functions in providing public services. Government social media management requires an organizational culture accompanied by support from all levels of government officials to be able to share information with the public. Utilization of E-Government which is intended to make management and government work more effective, efficient, responsive, transparent and accountable. E-Government is a basic and standard procedural approach related to public administration. The widespread use of social media shows supply-driven symptoms. E-Government is present in a demand-side character. This research wants to answer how the pattern of interaction between the government and the community can optimize the use of social media